Λ-carrageenan exacerbates Citrobacter rodentium-induced infectious colitis in mice by targeting gut microbiota and intestinal barrier integrity. (December 2021) - Wu, Wei; Zhou, Dongsheng; Xuan, Rongrong; Zhou, Jiawei; Liu, Jingwangwei; Chen, Juanjuan; Han, Hui; Niu, Tingting; Li, Xingxing; Chen, Haimin; Wang, Feng
Abstract: For nearly half a century, the scientific community has been unable to agree upon the safety profile of carrageenan (CGN), a ubiquitous food additive. Little is known about the mechanisms by which consumption of CGN aggravates the etiopathogenesis of murine colitis. However, analyses of gut microbiota and intestinal barrier integrity have provided a breakthrough in explaining the synergistic effect of CGN upon colitis. In Citrobacter rodentium -induced infectious murine colitis, inflammation and the clinical severity of gut tissue were aggravated in the presence of λ-CGN. Using fecal transplantation and germ-free mice experiments, we evaluated the role of intestinal microbiota on the pro-inflammatory effect of λ-CGN. Mice with high dietary λ-CGN consumption showed altered colonic microbiota composition that resulted in degradation of the colonic mucus layer, a raised fecal LPS level, and a decrease in the presence of bacterially derived short-chain fatty acids (SCFAs). Mucus layer defects and altered fecal LPS and SCFA levels could be reproduced in germ-free mice by fecal transplantation from CGN-H-fed mice, but not from germ-free CGN-H-fed mice. Our results confirm that λ-CGN may create an environment that favors inflammation by altering gut microbiota composition and gut bacterial metabolism. The present study provides evidence that the "gut microbiota-barrier axis" could be an alternative target for ameliorating the colitis promoting effect of λ-CGN. Graphical Abstract: ga1